2019
DOI: 10.1109/access.2019.2950656
|View full text |Cite
|
Sign up to set email alerts
|

Platforms for Smart Environments and Future Internet Design: A Survey

Abstract: Internet of things (IoT) is pushing the integration of physical and virtual worlds. Sensor devices provide rich sensory information to context-aware services. Actuators implement in the physical world application needs. The role of software is increasing as more and more resources become virtualized and software-defined. Smart environment is an emerging concept that has the potential to address many of the humanity problems. In this context, what are the promising tools for building the smart environments of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 66 publications
0
14
0
1
Order By: Relevance
“…The notion of centralized decision making for the function implementation and configuration of forwarding nodes implies that the network control plane (which makes the decisions on the packet processing) is decoupled from the network data plane (which forwards the packets). Extending the principles of SDN from forwarding nodes to the broad notion of compute nodes can achieve more flexibilities in the deployment of NFs on GPC platforms in terms of scalability and management [10], [11]. More precisely, SDN can be applied for two primary purposes: i) macro-scale NF deployments, where the decisions involve selecting a specific platform for NF deployments based on decision factors, such as physical location, capabilities, and availability, and ii) micro-scale NF deployments, where the decisions involve reconfiguring the NF parameters during ongoing operations based on run-time requirements, such as traffic loads, failures and their restoration, as well as resource utilization.…”
Section: ) Network Functions (Nfs) and Network Function Virtualizatimentioning
confidence: 99%
“…The notion of centralized decision making for the function implementation and configuration of forwarding nodes implies that the network control plane (which makes the decisions on the packet processing) is decoupled from the network data plane (which forwards the packets). Extending the principles of SDN from forwarding nodes to the broad notion of compute nodes can achieve more flexibilities in the deployment of NFs on GPC platforms in terms of scalability and management [10], [11]. More precisely, SDN can be applied for two primary purposes: i) macro-scale NF deployments, where the decisions involve selecting a specific platform for NF deployments based on decision factors, such as physical location, capabilities, and availability, and ii) micro-scale NF deployments, where the decisions involve reconfiguring the NF parameters during ongoing operations based on run-time requirements, such as traffic loads, failures and their restoration, as well as resource utilization.…”
Section: ) Network Functions (Nfs) and Network Function Virtualizatimentioning
confidence: 99%
“…Few surveys specifically discuss certain layer [46] based on services and functions. 6 layers [30], [40], [87], [94] 5 layers [11], [24], [30], [31], [64], [78], [79], [94] 4 layers [10], [11], [38], [63], [64], [67], [75], [78], [80], [89], [90] 3 layers [20], [31], [32], [44], [62], [68], [78], [86], [88], [100] Specific layer [18], [31], [37], [46], [56], [68], [73], [79], [80] The percentages of the trend for the IoT architecture layers review, according to the layers classification, are shown in Fig. 7.…”
Section: Internet Of Things Architecturementioning
confidence: 99%
“…Physical/MAC [31], [38], [44], [56], [68], [73], [86], [87], [89], [ This paper suggests that the IoT architecture classification comprise 3 main layers with regards to the IEEE standards and the communication protocols in Table VI and VII. Possible research in IoT architecture must be able to match the 3-layer classification with functionalities and communication protocols.…”
Section: Internet Of Things Architecturementioning
confidence: 99%
“…Cloud computing can be considered a new generation of computing infrastructure; this technology enables users to use vast resources in terms of storage and processing provides quick access to available services on request [2]. The Internet of Things (IoTs) can affect changes in daily activities and behaviours [3], [4], [5], [6]. An IoT system may suffer from problems related to available resources in terms of transmission, storage, and processing.…”
Section: Introductionmentioning
confidence: 99%